2010
DOI: 10.1016/j.febslet.2010.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical organization of the plasma membrane: Investigations by single‐molecule tracking vs. fluorescence correlation spectroscopy

Abstract: a b s t r a c tSingle-molecule tracking and fluorescence correlation spectroscopy (FCS) applied to the plasma membrane in living cells have allowed a number of unprecedented observations, thus fostering a new basic understanding of molecular diffusion, interaction, and signal transduction in the plasma membrane. It is becoming clear that the plasma membrane is a heterogeneous entity, containing diverse structures on nano-meso-scales (2-200 nm) with a variety of lifetimes, where certain membrane molecules stay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
1
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(164 citation statements)
references
References 105 publications
(191 reference statements)
9
148
1
6
Order By: Relevance
“…With a close examination, our results resemble the hop diffusion described by Kusumi based on 40 nm gold particle tracking (Fig. 3 A) (101). Although the conventional 2D-SPT results suggested that all phospholipid and transmembrane proteins exhibit short-term confined diffusion within a compartment and long-term hop movement from one domain to another (socalled the skeleton fence model) (101), more-advanced techniques, such as the scanning STED-FCS that provides even higher spatiotemporal resolution in molecular motion analysis, showed no evidence of nanodomains but rather suggested transient interactions with immobile or slowly moving entities, possibly proteins (102).…”
Section: Challenges In Molecular Trajectory Analysissupporting
confidence: 85%
“…With a close examination, our results resemble the hop diffusion described by Kusumi based on 40 nm gold particle tracking (Fig. 3 A) (101). Although the conventional 2D-SPT results suggested that all phospholipid and transmembrane proteins exhibit short-term confined diffusion within a compartment and long-term hop movement from one domain to another (socalled the skeleton fence model) (101), more-advanced techniques, such as the scanning STED-FCS that provides even higher spatiotemporal resolution in molecular motion analysis, showed no evidence of nanodomains but rather suggested transient interactions with immobile or slowly moving entities, possibly proteins (102).…”
Section: Challenges In Molecular Trajectory Analysissupporting
confidence: 85%
“…Hormone-treated LH receptors were not confined in small membrane compartments when treated with cytochalasin D, a disruptor of the actin-based cytoskeleton (34 -37), suggesting that the compartments evaluated with single particle tracking methods are bounded by protein fences or cytoskeletally anchored protein networks that limit lateral diffusion of transmembrane proteins (6). It is also possible that the restriction of LH receptor lateral motions involves both lipid rafts and protein delineated networks nested in a hierarchical fashion as has been proposed recently (50).…”
Section: Discussionmentioning
confidence: 90%
“…8. These microdomains could also be associated with lipid rafts (Jacobson et al, 2007;Kusumi et al, 2010). Partitioning the membrane into a set of corrals implies that anomalous diffusion of proteins will be observed on intermediate timescales, due to the combined effects of confinement and binding to the actin cytoskeleton.…”
Section: Diffusion In the Plasma Membranementioning
confidence: 99%
“…This follows from the hydrodynamic membrane diffusion model of Saffman and Delbruck (Saffman and Delbruck, 1975), which implies that the diffusion coefficient for a cylinder of radius r in a 2D membrane varies as log r. Although the diffusion of lipids appears to be Brownian in pure lipid bilayers, single-particle tracking experiments indicate that lipids and proteins undergo anomalous diffusion in the plasma membrane (Feder et al, 1996;Kusumi et al, 2005;Saxton and Ja- cobson, 1997). This has led to a modification of the original fluid mosaic model, whereby lipids and transmembrane proteins undergo confined diffusion within, and hopping between, membrane microdomains or corrals (Kusumi et al, 2005(Kusumi et al, , 2010Vereb et al, 2003); the corraling could be due to "fencing" by the actin cytoskeleton or confinement by anchored protein "pickets", see Fig. 8.…”
Section: Diffusion In the Plasma Membranementioning
confidence: 99%